Survivability of embedded microelectronics in precision guided projectiles: Modeling and characterization - Verberne, P.; Meguid, S.A.; Elsayed, E.A. (International journal of impact engineering, 2021)
•Developed a new polymeric encapsulation technique to protect embedded MEMS.•Tested the efficacy of the encapsulation technique using instrumented drop weight.•Developed multi-level micromechanics schemes to determine effective properties of encapsulant components.•Identified trilayer encapsulant arrangements as best choice for attenuating shock loads. Precision guided projectiles (PGPs) experience severe shock loads during launch emanating from the propellant gasses and the surrounding air. Our most recent multiphysics effort showed that the complex flow environment during launch would result in the development of severe shock loads in the confined barrel space and at muzzle exit. The focus of the current effort is the survivability of the embedded integrated circuit chips and printed circuit boards (PCB). Four aspects of the work were accordingly examined. The first is concerned with the development of a new polymeric encapsulation technique to protect the embedded microelectronic systems (EMES). The second with testing the effectiveness and endurance of the newly proposed encapsulation techniques using instrumented pneumatic drop weight impact test facility. The third with constructing bottom-up multi-level micromechanics based homogenization schemes, accounting for complex constitutive material models of a multilayer circuit board, to determine the effective elastic properties of the PCB for the numerical FE simulations. The fourth with conducting three-dimensional high-resolution dynamic FE simulations to evaluate the structural integrity of the potted PCB assembly in response to the short duration impulse and to elucidate the experimental findings. The results of our experimental and numerical efforts reveal that the newly devised encapsulation technique is highly effective in protecting EMES and can be used to audit the survivability of the microelectronics that are embedded in PGPs.